PENGGUNAAN METODE DYNAMIC PROGRAMMING UNTUK ANALISIS URUTAN PENGGUNAAN MESIN PROSES PRODUKSI PRODUK DEPAKOTE - Budihardjo, Iwan; -, Muchdopir (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
A recurring problem in the industry is to determine the order of machines to be used in production in order to get optimal results. The method used to solve this problem is by using a model of Budgeting Capital from Dynamic Programming. With this model each phase of the process may be called a stage and each machine is considered as a state, where each stage and the state have a mutual relationship as a whole. The model resulted is the following order of the machines, the granulator to process Meshing, Drum Rotator for Mixing, Reynold for Wet Granulation, Static Oven for Drying, Killian RUZS for Compressing and for the coating process Accelacota 48" is used. Total time used for the process is 1445 minute with a time saving of 805 minutes. The time savings enables the company to reduce production costs of machinery and wage labor costs, therefore iti si recommended that this optimal order machinery is applied in the production of Depakote in the future.